Pengaruh Stres Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Mediasi Pada PT SEMEN TONASA - Anita, Andi Reski Nur; Sahabuddin, Romansyah; Musa, Muh. Ichwan; Burhanuddin; Natsir, Uhud Darmawan (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of work stress and work environment on employee performance with job satisfaction as a mediating variable at PTV Semen Tonasa. This study uses a quantitative approach with Partial Least Square (PLS) analysis technique. The research sample consists of PT Semen Tonasa employees selected through purposive sampling technique. The results of the study indicate that work stress has a negative but significant effect on employee performance, while the work environment has a positive and significant effect. In addition, work stress does not have a significant effect on job satisfaction, while the work environment has a significant effect on job satisfaction. Job satisfaction is proven to have a significant effect on employee performance and is able to mediate some of the influence of the work environment on performance, but does not mediate the effect of work stress. The findings of this study emphasize the importance of stress management and creating a conducive work environment to improve employee satisfaction and performance.